Investigating Lexical And Syntactic Ambiguity On Native Facebook Celebritism - juliana juliana; Nadirah Nadirah; Lababa Lababa; Ibrahim Manda; Sam hermansyah . (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
The objectives of the research are to know why do many readers not understand about the meaning of the facebook post by native facebook celebritism and to find out the types of ambiguity and dominant type of lexical and syntactical ambiguity use in Facebook Post by native facebook celebritism.In this research, researcher applied desriptive qualitative method. Qualitative research, like other types of research, is descriptive, with data collected in the form of words or images rather than numbers. Choosing, reading, and underlining were the methods used to collect data. Identifying, classifying, analyzing, calculating, and interpreting the data were all used to analyze the data. Homonymy, polysemy, synonymy, and antonymy were among the linguistic ambiguities. Surface structure ambiguity and deep structure ambiguity were the two types of syntactical ambiguity.